PENGARUH PENERAPAN AKUNTANSI PEMERINTAHAN DAN KUALITAS INFORMASI AKUNTANSI TERHADAP GOOD GOVERNMENT GOVERNANCE SERTA IMPLIKASINYA TERHADAP KINERJA KEUANGAN PADA SKPD SE KOTA MEDAN - Fitriani Saragih (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research purpose to determine the influence of the Governmental Accounting Application and Accounting Information Quality Governance against Good Government and the implication of Financial Performance.The research was conducted on regional work units (SKPD) Medan using the census method. The data was collected by spreading questionnaire questionnaires and browshing in Medan City Government Website .. Data analysis and hypothesis testing is done using multiple regression analysis and simple.The results showed that (1) The application of government accounting, accounting information quality governance and good government that does not have a significant influence on financial performance SKPD in Medan. Influence the application of government accounting, accounting information quality governance and good government that does not have a significant influence on financial performance in the city of Medan SKPD low at 17.4% (2) The application of governmental accounting and accounting information quality has a significant influence on good government governance SKPD in Medan.  Influence the application of government accounting and accounting information quality on good government governance SKPD in Medan is high at 33.3%. (3) The application of governmental accounting and accounting information quality has no significant influence on financial performance SKPD in Medan. Influence the application of government accounting and accounting information quality on financial performance in the city of Medan SKPD low at 11.5%. (4) Good governance government has no significant influence on financial performance SKPD in Medan. The influence of good government governance to financial performance SKPD in Medan is very low at 0.1%.Keywords: Government Accounting, Accounting information, Good Government Governance,  Financial performance